Study on Flood Management Plan in Surabaya City - Anton Dharma Pusaka Mas (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
The area alongside the Gunung Sari Channel has an important meaning to the development of Surabaya City. The rising development in this area which causes the increase of flood events induces negative impacts on the growth of Surabaya City. The flood management plan in Gunung Sari Channel has been conducted by Brantas Project since 1988. This planning was reviewed in 1993 and 1999. This research was conducted to analyze the performance of flood management plan by Brantas Project. It was constructively done by HEC-FDA Software which can develop risk analysis by including economic consideration. Hydro-Economy approach integrated with the HEC-FDA analysis can yield the indicator of flood management plan performance in the form of total cost and risk cost (Expected Annual Damage/EAD). The best total cost yielded from the analysis was Rp. 893,692,230, while the risk cost was Rp. 384,238,410/year. It is expected that this research result can used for achieving best performance for floods management in Gunung Sari Channel.